Drivers of European public debt management - Guido Franciscus Theodorus Wolswijk (European Central Bank (ECB), 2020)
This study analyses the choice of government debt managers in the euro area between issuing short-term or long-term debt over the period 1992-2017. Debt managers increased short-term debt issuance in response to higher interest rate spreads and to rising government debt, notably in vulnerable, high-debt countries. Thus, lower longterm rates as a result of ECB's Quantitative Easing (QE) triggered debt managers to focus debt issuance on the long-term end. Moreover, the usual increase in debt maturity when debt rises ceases to operate when QE is active, possibly because markets perceived it as a backstop to the government bond market. However, limited QE experience calls for caution in interpreting the results.
Keywords: H63; G12; 330; debt maturity; Quantitative Easing; debt management; reaction function